(untitled) (American Journal of Technology and Applied Sciences, 2025)
This article includes the intersection of utopian motifs and the construction of national identity in American literary tradition. By examining significant texts from different historical periods, the research highlights how utopian narratives contribute to shaping, challenging, and reaffirming concepts of American identity. The study also considers how these literary works reflect changing social, political, and cultural contexts while offering alternative visions of the nation’s future.